PENGEMBANGAN SISTEM INFORMASI PADA KLINIK KENANGA DENGAN METODE RAD (RAPID APPLICATION DEVELOPMENT) - Irfan Afriantoro; Nurhadi Surojudin (Jurnal Pelita Teknologi, 2021)
Clinics are health service facilities that provide individual health services providing basic or specific medical services. Kenanga Clinic and Maternity Home have not been optimal in the use of information technology in some of their work systems, one of which is the registration section which still uses paper-based bookkeeping media. This causes several obstacles that often prevent clinic staff or clinic management from obtaining information related to registration data and medical records. Based on the problems faced, the writer concludes the formulation of the problem, namely, how to make a system to store patient data to make it better. The purpose of this research is to develop a clinical information system for patient data at the Kenanga clinic, which currently does not have an information system. The system development method used by the author is Rapid Application Development. RAD is a systems development strategy that emphasizes speed of development through extensive user involvement in construction, fast, iterative and incremental. Based on the research that has been done, the authors can conclude that the patient registration information system makes it easier to store patient data and staff can work well. In addition, this patient registration information system makes it easier to report patient data because the input data has been recorded automatically and is running well.